2023
DOI: 10.3390/bios13020152
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Volatile Fatty Acids in Silage through Odors with Nanomechanical Sensors

Abstract: The measurement of volatile fatty acids (VFAs) is of great importance in the fields of food and agriculture. There are various methods to measure VFAs, but most methods require specific equipment, making on-site measurements difficult. In this work, we demonstrate the measurements of VFAs in a model sample, silage, through its vapor using an array of nanomechanical sensors—Membrane-type Surface stress Sensors (MSS). Focusing on relatively slow desorption behaviors of VFAs predicted with the sorption kinetics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This is because sensing signal of nanomechanical sensors in static mode operation is obtained from sorption-induced expansion, , which is governed by sorption kinetics as long as the absorbed molecules including water do not exceed the capacity of receptor materials. It should be noted that the signal responses of PMMA to aldehydes fluctuated significantly under the humidified conditions because PMMA has hydrophilic nature and is sensitive to water . This led to poor fitting results.…”
Section: Resultsmentioning
confidence: 99%
“…This is because sensing signal of nanomechanical sensors in static mode operation is obtained from sorption-induced expansion, , which is governed by sorption kinetics as long as the absorbed molecules including water do not exceed the capacity of receptor materials. It should be noted that the signal responses of PMMA to aldehydes fluctuated significantly under the humidified conditions because PMMA has hydrophilic nature and is sensitive to water . This led to poor fitting results.…”
Section: Resultsmentioning
confidence: 99%
“…For simplified monitoring the degree of aerobic deterioration, so far, changes in temperature or pH have been used as indicators (Shan et al, 2021). We recently demonstrated that one of the nanomechanical sensors MSS for detecting VFAs in silage and showed the sufficient discrimination of the silage samples (Minami et al, 2023). This sensor has clearly discriminated the quality of corn silage used in this study, and feeding trial was conducted for practical use of devise.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of corn silage has been shown in a previous report (Minami et al, 2023). Briefly, whole plant corn (Zea mays L.) was mown at the yellow ripe stage and ensiled in an underground silo for six months.…”
Section: Preparation Of High and Low Quality Corn Silagementioning
confidence: 99%
See 2 more Smart Citations